Day to Day the Relationship Way Creating Responsive Programs for Infants and Toddlers. - Wittmer, Donna S. (National Association for the Education of Young Children, 2020)
Focus on the wonder of learning with infants, toddlers, and twos. Use sensitive and responsive interactions and curriculum planning that support their development as effective communicators, problem solvers, and creative thinkers.